THE PROHIBITION OF TORTURE, CRUEL OR DEGRADING TREATMENT OR PUNISHMENT IN CLOSED INSTITUTIONS - Girfanova, Jelena (Administrative and Criminal Justice, 2021)
In the paper “The prohibition of torture and other cruel, inhuman or degrading punishment in closed Institutions” the author has examined the obxervasnce of persons’ in detention, custody or imprisonment human rights in the European regional acts and national instruments as well as the provision of health care for detainees and convicted persons alike.All basic human rights’ documents, namely: the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the United Nations and the European Convention for the Protection of Human Rights and Fundamental Freedoms state that “no one shall be subjected to torture or to cruel, inhuman or degrading treatment or punishment, degrading his or her human dignity”. All persons who have been punished, regardless of the crimes for which they were convicted, have the right to humane treatment and respect for their personality. No actions of people, whatever they may be, justify the inhuman treatment of them or the humiliation of their personality.